Content Based Image Retrieval using Learnt Features from Convolution Neural Networks - Bhandi, Vijayakumar; Devi, Sumithra K.A (International Journal of Computer Sciences and Engineering, 2025)
Content based image retrieval (CBIR) relies on fetching relevant images from a dataset based on low level image features. Image features such as colour, texture and shape have been widely used in CBIR applications. These handcrafted features have been carefully designed and found to perform well in image retrieval task. The performance of these features greatly depends on the choice of the handcrafted features being used and domain knowledge. Hence there is a need to identify image features which are independent of domain knowledge and can be dynamically extracted from image data. Machine learning is a promising area here, since it focuses on learning representations from input data. Machine learning methods have been applied in various image processing tasks earlier. Convolution neural networks (CNN) models are able to create expressive features from image data and are successfully applied in image classification tasks. In this paper, we create a frame work to use CNNs to learn features from the image data and use these learned features for content based image retrieval. We test our proposed CBIR framework to retrieve images from a digital library database of art images. The results are compared against standard CBIR model which uses global colour histogram handcrafted feature. The results show that the learnt features extracted from a CNN model perform equally good as handcrafted features when applied to image retrieval task